Control over the complex phase evolutions for ultrahigh dielectric energy storage in pure poly(vinylidene fluoride) films. (25th November 2022) - Liu, Huan; Wang, Ziyue; Xie, Jiyang; Guo, Changjin; Hu, Wanbiao
Abstract: Poly(vinylidene fluoride) (PVDF) is a basic polymer that has been extensively used in flexible electronics, with the properties differing in terms of multiple phases, e.g. α, β, and γ . As generally involved, processing induced phase variations have not yet been identified clearly, which furthermore often embarrasses the attributions and contributions in the properties and mechanisms. To this end, the phase compositions and evolutions in pure PVDF films are systematically tuned and explored by annealing and quenching processing. The annealed PVDF exhibits a predominant γ -phase, while α -phase is dominated in quenched PVDF. Upon the induced different phase compositions, the optimally processed PVDF films similarly exhibit an ultrahigh dielectric energy storage density e.g. 19.66 J cm −3 for annealed and 21.73 J cm −3 for quenched PVDF film, respectively, but only the former maintains a simultaneously high discharge efficiency of 65 %. With showing excellent energy storage performance, the processed especially the annealed PVDF film could compare to many existing high-performance dielectric energy storage systems. This work thus not only uncovers the phase evolutions as well as their impacts on the properties in PVDF system, but also demonstrates firstly a high energy storage performance in pure PVDF. Graphical abstract: Pure PVDF films is fabricated by a solution casting method and further processed by the controlled annealing and quenching to investigate the phase evolutions and properties. The annealed PVDF film shows an ultrahigh energy density of 19.66 J cm −3 and high discharge efficiency ( 65 %), which demonstrates firstly a high energy storage performance in pure PVDF. Unlabelled Image Highlights: Phase compositions and evolutions in pure PVDF films are systematically tuned and explored by annealing and quenching processing. The processed PVDF films similarly exhibit an ultrahigh dielectric energy storage density e.g. 19.66 J/cm 3 for annealed and 21.73 J/cm 3 for quenched PVDF film, respectively. This work demonstrates firstly a high energy storage performance in pure PVDF.